Clinical and Apoptotic Factors Defining and Predicting Steroid Resistance in Nephrotic Syndrome in Children - Ievgeniia Burlaka MD, PhD; Inga Mityuryayeva MD, PhD, Prof; Ingretta Bagdasarova MD, PhD, Prof (SAGE Publishing, 2022)
Introduction. Nephrotic syndrome (NS) is a kidney disease characterized by albuminuria, hyperlipidemia, edema, and hypoalbuminemia. Above 20 % of nephrotic children do not show response to steroid treatment. Molecular markers controlling apoptosis have not been studied as a predictors of steroid resistant NS (SRNS) and steroid sensitive NS (SSNS) in children. Aim of the Study . To identify clinical and molecular markers which define and predict the steroid-resistance phenomenon in children with NS. Methods . Fifty-six clinical cases of children hospitalized in Pediatric Hospital No. 7 (Kyiv, Ukraine) with NS (26 SSNS and 30 SRNS) studied. Stepwise logistic regression models used to analyze data. Data processed using GraphPad Prism 9.0 Software for Windows (USA, San Diego, CA). Results. Arterial hypertension, WBC and RBC count, serum creatinine, serum urea, serum cholesterol found to be factors defining and predicting SRNS. Apoptosis regulating BcL-xL, Bax but not caspase-8 found to be those defining SRNS. Among transcriptional factors HIF-1alfa selected as a factor predicting steroid resistance phenomenon. For SSNS group significant negative correlation observed between BcL-xL and Bax, BcL-xL and caspase-3, significant positive correlation observed between marker of cellular hypoxia HIF-1alfa and proapoptotic factor caspase-3. For SRNS group significant negative correlation observed between BcL-xL and Bax, BcL-xL and caspase-3 level, significant positive correlation observed between HIF-1alfa and proapoptotic factor caspase-3. Conclusions . Arterial hypertension, serum creatinine level, serum urea level, serum cholesterol level, WBC and RBC count, BcL-xL, Bax, caspase-3, and HIF-1alfa identified as candidate biomarkers to predict and define SRNS in pediatric NS.